To J. Maddonald Kınneır Cyprus: Famagusta, Larnaca, Nıcosıa - Kuş, Ayşegül (Fırat University, 2019)
Cyprus is one of the three islands of the Mediterranean. Due to its geo-strategic position it has drawn the attention of the people and has become an important settlement since the early periods. Firstly, the island is on the location which dominates the Mediterranean region and due to this fact from past to present it has become the focus of interest of many different states which aimed to establish domination. In fact, throughout the course of history nearly every state which emerged in Anatolia, Syria, North Africa, and Europe tried to establish domination over Cyprus and as an island Cyprus was exposed to many invasions and conquests. The Ottomans, being eager to expand and guarantee their domination over the island, conquered the island in 1571 and made it the part of their homeland. Thus the island became an important center of the Turkish-Islamic culture. Cyprus, one of the most frequently visited places by travelers from the ancient times on also drew the attention of some of the Western travelers having viisted the Ottoman lands.  Those travelers narrated their own observations regarding the island, and they provided important information which can help us to understand the historical and socio-cultural development of the island. One of these travellers having narrated his own observations related to the island is J. McDonald Kinneir, who visited the island in the first half of the 19th century.  Making use of his travelogues, the aim of this study is to try to enlighten the physical, geographic, administrative, political and socio-cultural structure of the island and make some contributions to the history of thei sland.

Kıbrıs, Akdeniz’in üç büyük adasından birisidir. Jeo-stratejik konumu gereği erken dönemlerden beri, insanlığın ilgisini çekmiş ve önemli bir yerleşim merkezi olmuştur. Ada, her şeyden önce, eski ve büyük bir uygarlık beşiği olan Akdeniz havzasına hâkim bir konumdadır ve bu özel durumu nedeniyle, geçmişten günümüze bu bölgelerde hâkimiyet kurmak isteyen pek çok devletin ilgi odağı olmuştur. Nitekim tarihsel süreç içerisinde Anadolu, Suriye, Kuzey Afrika ve Avrupa’da ortaya çıkan hemen her devlet, Kıbrıs adası üzerinde hâkimiyet tesis etmeye çalışmış; bir ada olarak Kıbrıs, pek çok istilalara ve fetihlere sahne olmuştur. Osmanlılar da, Akdeniz üzerindeki hâkimiyet alanını genişletmek ve garanti altına almak için, 1571’de adayı fethetmişler ve kendi topraklarının bir parçası haline getirmişlerdir. Böylelikle ada, Türk-İslam uygarlığının önemli merkezlerinden birisi haline gelmiştir. Tarih öncesi dönemlerden itibaren çok sayıda seyyahın uğrak yerlerinden birisi olan Kıbrıs, Osmanlı topraklarına gelen kimi batılı seyyahların da dikkatini çekmiştir. Bu seyyahlar, ada hakkında gözlemlerini aktarmışlar, adanın tarihsel ve sosyo-kültürel gelişimini anlamamıza olanak sağlayacak önemli bilgiler sunmuşlardır. Ada hakkında gözlemlerini aktaran önemli seyyahlardan birisi de, 19. yüzyılın ilk yarısında Kıbrıs’ta bulunan İngiliz seyyah J. McDonald Kinneir’dir. İşte bu çalışmanın amacı,  onun gezi notlarından yola çıkarak adanın o dönem içinde bulunduğu fiziki, coğrafi, idari, siyasi ve sosyo-kültürel durumuna ışık tutmak ve adanın tarihine kimi katkılar sağlamaktır.
J. MACDONALD KINNEIR’E GÖRE KIBRIS: MAĞUSA, LARNAKA, LEFKOŞA